THE CAPOEIRA AND ITS PAPER WHILE AGENT OF SOCIAL TRANSFORMATION: THE CASE OF PROJECT CAPOEIRA AND CITIZENSHIP KEPT FOR THE VIKING ASSOCIATION (Fiep Bulletin - online, 2014)
The objective of this study is to perceive and to stand out the importance of the Capoeira while half of Education of transmission of social values. It is possible to point out that when establishing the bridges between the knowledge accumulated in the human development, in its varied flowing, we primamos for adequate the educative valuation of a manifestation riquíssima that beyond all the advantages still are proper and exclusive of the Brazilian people. For in such a way the comment of the development of the Project Capoeira and Cidadania, kept for the Association of Employees of the Volvo of Brazil, the Viking Association fits, through the Law of Incentive to the Culture (Law n º 8,313/91). The Project takes care of seventy young of seven to dezessete years of age and not only aims at the formation of athletes technical prepared well, but mainly, the formation of responsible and conscientious individuals of its paper while citizens. The results until gotten here are fruit of great quarrel, reflection and analysis on the part of its idealizers and mantenedores, which join its "to know" to the ones of the proper participants of the Project in an incessant search for social transformations that can come to contribute for the construction of a society each better day and more human being.
Keywords: Capoeira; Project of Social Action; Citizenship